Analisis Phone Snubbing Behavior Mahasiswa - Windasantika; Nurhanifah (Perspektif Ilmu Pendidikan, 2023)
The phenomenon of phubbing is inherent in all circles, especially students, phubbing behavior shows impolite behavior and has an impact on communication between individuals when communicating. This study uses a qualitative method with a phenomenological study. Data collection techniques were carried out using open interview methods. 10 Respondents from this study came from universities in Indonesia represented by several universities, including the State Islamic University of North Sumatra, Suska Riau State Islamic University, Medan Area University, North Sumatra Muhammadiyyah University, Panca Budi University, Medan Polytechnic, Mallikussaleh University, University Open, Islamic Religion Daar Al Uluum (IAIDU) Asahan, Asahan University. The technique used in selecting respondents is probability sampling. The analysis used is qualitative techniques, in-depth analysis and interpretive phenomenology. The aim is to analyze Phone Snubbing Behavior among students. The results of the study show that phubbing behavior for students has often been carried out so that it has an impact on interactions between families, romance and friendships. These results indicate that students are unintentionally accustomed to phubbing.